Flexoelectric effect driven colossal triboelectricity with multilayer graphene - Kumar, Mohit; Lim, Jaeseong; Park, Ji Yong; Seo, Hyungtak (Current Applied Physics, 2021)
Converting mechanical deformation from surrounding environment into detectable electrical signals remains one of the most attractive fields due to its potential applications in sustainable energy harvesting, self-powered sensors, and others. Presently, deformation energy is harvested by generating voltage/current through bending/twisting of piezoelectric materials, but its recyclability is limited in number. In contrast, polarization is generated in all known insulators/semiconductors due to elastic strain gradient, which offers unique electromechanical coupling and in turn, could generate significant potential differences to drive charge transfer. Here, we demonstrate that extremely high direct current with density of 28 × 106 A m−2 is generated without need of any external power supply by applying pointed force using conductive-atomic force microscope (cAFM) tip on multilayer graphene/substrate (SiO2, Si, glass). Further, the ramp-dependent time-resolved current is measured at a localized point, which indicates that pointed force-induced flexoelectric potential differences are the main driving factor to utilize mechanoelectrical coupling and in turn generate high current density. This research work provides a new strategy to utilize the flexoelectric effect to utilize electromechanical coupling to generate giant energy harvesting, which will have a potential impact on the various multiple fields including smart devices, materials, and even a fundamental understanding of physics.
Keywords: Conductive atomic force microscopes; Current generator; DC current generator; Flexoelectric effects; Flexoelectricity; Mechanical deformation; Multilayer graphene; Potential difference; Self-powered; Surrounding environment; cAFM; DC current Generator; Flexoelectricity; Self-powered; Triboelectricity